The Impulsive Buying Behavior of H&M Products in Gen-Z: The Role of Income and Self-Esteem - Nastasya Ryoko Bonang Tessy; Setiasih Setiasih (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2024)
Generation Z is currently the largest consumer in Indonesia; thus their values and priorities could lead to changes in consumption patterns and societal norms. This study examined the influence of income, self-esteem, and impulsive buying behavior of H&M products in Gen-Z. This research was conducted using a quantitative cross-sectional with a predictive design. Research respondents were obtained through a non-random accidental sampling of 374 Gen-Z who had made unplanned purchases of clothes from the H&M brand at least once in the past month. Data analysis was performed using correlation and multiple regression tests. The results showed that income and self-esteem could be used as predictors of impulse buying behavior. However, the income itself showed no contribution when self-esteem was controlled. Research implies that monitoring self-esteem and using interventions to increase self-esteem could help control impulse buying behavior that individuals, especially Gen-Z, usually do.